An Approach for efficient implementation of Uncertainty Analysis in Production-Related Measurement Processes. - Timmermann, Martin; Werner, Teresa; Weckenmann, Albert (Proceedings of the 14th Joint International IMEKO TC1 + TC7 + TC 13 Symposium, 2011)
The statement of measurement uncertainty with a given measurement result provides valuable information about its quality and reliability. In the ISO/BIPM Guideline to the Expression of Uncertainty in Measurements (GUM), a commonly accepted procedure to evaluate the uncertainty is described. Yet for measurement results in manufacturing metrology, measurement uncertainty is only rarely evaluated and stated, because the procedure based on GUM is considered as too complicated. To solve this problem, an assistance system is developed to support the analysis of measurement uncertainty in companies as well as enhance a workflow optimized procedure for the evaluation. As a prerequisite for the implementation of such an assistance system, generic processes have been defined, splitting up the steps of uncertainty evaluation and implementing them in typical processes of production metrology. These generic processes open up the possibility to implement the GUM steps into any existing processes among companies and allow a comprehensive and coordinated determination and evaluation of the measurement uncertainty based on the GUM. This implementation of processes for measurement uncertainty evaluation contributes towards providing the required accuracy for the production processes as well as the customers’ demands to qualit
Keywords: Uncertainty analysis; manufacturing metrology; knowledge management